Glutamatergic Modulators in Depression. Issue 6 (November 2018) - Henter, Ioline D.; de Sousa, Rafael Teixeira; Zarate, Carlos A.
Abstract : Learning objective: After participating in this activity, learners should be better able to evaluate the evidence supporting the antidepressant effects of glutamatergic modulators. Both preclinical and clinical studies have implicated glutamatergic system dysfunction in the pathophysiology of mood disorders such as bipolar depression and major depressive disorder. In particular, rapid reductions in depressive symptoms have been noted in response to subanesthetic doses of the glutamatergic modulator ketamine in subjects with major depressive disorder or bipolar depression. These results have prompted the repurposing or development of other glutamatergic modulators, both as monotherapy or adjunctive to other therapies. Here, we highlight the evidence supporting the antidepressant effects of various glutamatergic modulators, including (1) broad glutamatergic modulators (ketamine, esketamine, dextromethorphan, dextromethorphan-quinidine [Nuedexta], AVP-786, nitrous oxide [N2 O], AZD6765), (2) subunit (NR2B)-specific N-methyl-D-aspartate (NMDA) receptor antagonists (CP-101, 606/traxoprodil, MK-0657 [CERC-301]), (3) glycine-site partial agonists (D-cycloserine, GLYX-13, sarcosine, AV-101), and (4) metabotropic glutamate receptor modulators (AZD2066, RO4917523/basimglurant, JNJ40411813/ADX71149, R04995819 [RG1578]).